INTEGRITAS LAPORAN ARUS DANA, ARUS KAS, DAN INFORMASI PROBABILITAS DALAM PRAKTIK PELAPORAN KEUANGAN MODERN - Christian Damar Sagara Sitepu; Destriana Putri; Nur Gustiani Ratu Sindang; Shafira Jasmine Qatari Firman (PT. Hasba Edukasi Mandiri, 2025)
This study examines the integrity of fund flow reports, cash flow statements, and probabilistic information in modern financial reporting practices. Reporting integrity has become a crucial concern as business transactions grow more complex and predictive technologies expand. A quantitative approach using multiple linear regression was employed to analyze the influence of these variables on the integrity of financial reports issued by public companies in Indonesia. The findings reveal that fund flows, cash flows, and probabilistic information significantly affect reporting integrity, with cash flow being the most dominant contributor. Moreover, transparently presented probabilistic information strengthens the credibility of financial statements. These results highlight the need for consistency, methodological clarity, and strong governance to ensure that modern financial reporting remains reliable and trustworthy to stakeholders.